Motivasi Kerja, Sertifikasi, Kesejahteraan dan Kinerja Guru - Zulkifli, Mohammad; Darmawan, Arif; Sutrisno, Edy (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2014)
Abstract. This cross-sectional study empirically examines the motivation and certification as antecedent welfare and performance of teachers and welfare as antecedent performance. Slovin formulation is used to take a sample of 244 teachers. Samples were taken from a population of 624 teachers who are already certified. Testing the model fit using Structural Equation Modeling. The test results demonstrate the value of Ï‡2 = 449.163; p = 0.542; RMSEA = 0.000; GFI = 0.901; AGFI = 0.884; CMN / DF = 0.991; TLI = 1.001, and; CFI = 1.000. Results Analysis of Moment Structures / AMOS all support the model fit hypothesis. The findings of the study stated motivation and certification plays an important role in efforts to enhance the welfare and performance of teachers. Teacher performance can be predicted through the welfare of teachers. The research findings will be discussed in the context of motivational teacher certification program.Keywords: motivation, certification, welfare, performance